2019
DOI: 10.1111/vec.12918
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of whole body computed tomography in polytrauma patients

Abstract: Objective:To determine the safety, feasibility, and utility of whole body computed tomography (WBCT) in polytrauma patients. A second objective was to describe the utilization of the Vet-Mouse Trap for sedated WBCT in polytrauma patients. Methods:A prospective, observational study in a high-volume private practice. Any cat or dog weighing <20 kg that presented to the emergency department following a polytrauma was eligible. Patients were given analgesia and sedation prior to placement in the VetMouse Trap. A W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 20 publications
(25 reference statements)
0
16
0
Order By: Relevance
“…In veterinary patients, limitations of WBCT in comparison to traditional diagnostic tests are comparative cost, feasibility due to equipment and staffing, and concerns for placing a hemodynamically unstable patient under anesthesia. A recent study found that the utilization of a transparent cylindrical restraint device c to perform sedated WBCT in polytrauma patients was a feasible modality for successful identification of injuries in sedated veterinary patients 32 . The aforementioned study demonstrated that good quality images were able to be obtained with the majority of patients being sedated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In veterinary patients, limitations of WBCT in comparison to traditional diagnostic tests are comparative cost, feasibility due to equipment and staffing, and concerns for placing a hemodynamically unstable patient under anesthesia. A recent study found that the utilization of a transparent cylindrical restraint device c to perform sedated WBCT in polytrauma patients was a feasible modality for successful identification of injuries in sedated veterinary patients 32 . The aforementioned study demonstrated that good quality images were able to be obtained with the majority of patients being sedated.…”
Section: Discussionmentioning
confidence: 99%
“…WBCT utilization in trauma patients has not been extensively studied in veterinary medicine due to concerns regarding cost, accessibility, and patient stability with regard to general anesthesia 32 . However, a recent study demonstrated successful use of WBCT in evaluation of small animal polytrauma patients with minimal sedation 32 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, CT has become increasingly used as a diagnostic tool for assessing traumatic injuries in veterinary medicine. [17][18][19] While CT scans require sedation in most patients, the use of head and whole body CT scanning following traumatic injuries provides detailed anatomical information at high resolution in a relatively short time. This wealth of cross-sectional data allows for accurate diagnosis and assists in treatment planning, including surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Thoracic and abdominal ultrasound (US), and computed tomography (CT) are also useful diagnostic imaging techniques for traumatized animals [ 42 , 43 , 44 , 45 ]. The US assessment of the thorax and abdomen is reported to be a rapid and accurate method to detect traumas in dogs [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…CT is considered the gold standard for the evaluation of acute canine spinal trauma [ 44 ]. It also appears to be more sensitive than ultrasound and radiography in the identification of thoracic pathologies in traumatized patients (i.e., pleural fluid, pulmonary contusion), but further studies are needed [ 45 ]. Thoracic or abdomen US or CT were not performed in the ungulates enrolled in this study; thus, a comparison between different diagnostic imaging procedures for the diagnosis of traumas was not possible.…”
Section: Discussionmentioning
confidence: 99%